Detection of PD-L1 Expression in Temozolomide-Resistant Glioblastoma by Using PD-L1 Antibodies Conjugated with Lipid‑Coated Superparamagnetic Iron Oxide - Lee GA (Dove Medical Press, 2021)
Gilbert Aaron Lee,1,2 Wan-Li Lin,1 Duen-Pang Kuo,3 Yi-Tien Li,4,5 Yu-Wei Chang,1 Yung-Chieh Chen,4,6 Shiu-Wen Huang,1,7,8 Justin Bo-Kai Hsu,1 Cheng-Yu Chen3,4,6,9 1Department of Medical Research, Taipei Medical University Hospital, Taipei, Taiwan; 2Department of Microbiology and Immunology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan; 3Department of Medical Imaging, Taipei Medical University Hospital, Taipei, Taiwan; 4Translational Imaging Research Center, Taipei Medical University Hospital, Taipei, Taiwan; 5Neuroscience Research Center, Taipei Medical University, Taipei, Taiwan; 6Research Center of Translational Imaging, College of Medicine, Taipei Medical University, Taipei, Taiwan; 7Department of Pharmacology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan; 8Graduate Institute of Medical Sciences, College of Medicine, Taipei Medical University, Taipei, Taiwan; 9Department of Radiology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, TaiwanCorrespondence: Cheng-Yu ChenDepartment of Radiology, School of Medicine, College of Medicine, Taipei Medical University, No. 251 Wu Hsing Street, Taipei City 110, Taipei, TaiwanEmail sandy0932@gmail.comPurpose: Targeted superparamagnetic iron oxide (SPIO) nanoparticles are a promising tool for molecular magnetic resonance imaging (MRI) diagnosis. Lipid-coated SPIO nanoparticles have a nonfouling property that can reduce nonspecific binding to off-target cells and prevent agglomeration, making them suitable contrast agents for molecular MRI diagnosis. PD-L1 is a poor prognostic factor for patients with glioblastoma. Most recurrent glioblastomas are temozolomide resistant. Diagnostic probes targeting PD-L1 could facilitate early diagnosis and be used to predict responses to targeted PD-L1 immunotherapy in patients with primary or recurrent glioblastoma. We conjugated lipid-coated SPIO nanoparticles with PD-L1 antibodies to identify PD-L1 expression in glioblastoma or temozolomide-resistant glioblastoma by using MRI.Methods: The synthesized PD-L1 antibody-conjugated SPIO (PDL1-SPIO) nanoparticles were characterized using dynamic light scattering, zeta potential assays, transmission electron microscopy images, Prussian blue assay, in vitro cell affinity assay, and animal MRI analysis.Results: PDL1-SPIO exhibited a specific binding capacity to PD-L1 of the mouse glioblastoma cell line (GL261). The presence and quantity of PDL1-SPIO in temozolomide-resistant glioblastoma cells and tumor tissue were confirmed through Prussian blue staining and in vivo T2* map MRI, respectively.Conclusion: This is the first study to demonstrate that PDL1-SPIO can specifically target temozolomide-resistant glioblastoma with PD-L1 expression in the brain and can be quantified through MRI analysis, thus making it suitable for the diagnosis of PD-L1 expression in temozolomide-resistant glioblastoma in vivo.Keywords: PD-L1, superparamagnetic iron oxide, SPIO, magnetic resonance imaging, MRI, lipid-coated nanoparticle, glioblastoma